Peluang Usaha Rumahan untuk Menciptakan Lapangan Pekerjaan (Donat dan Roti) di Desa Cikupa - Joko Supono; Puji Rahayu (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
Starting a home bakery and donut business is an attractive option for many individuals who have skills in cooking or baking, as well as an interest in the food industry. By taking advantage of time flexibility and lower initial costs than opening a physical store, this business offers the potential to generate additional income or even become a main source of income. Supporting quality and innovative food products on the menu can win the hearts of local customers and support the community economy. Although there are challenges in terms of licensing, operational management, and adapting to market changes, strategic steps in market research, business planning, product development, marketing, and inventory management can help build a successful and sustainable business in this sector. In conclusion, starting a bakery and donut business at home is not only about cooking skills, but also about creativity, effective business management, and commitment to providing added value to customers and the community as a whole.